2008
DOI: 10.1128/jcm.02015-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Influenza A Virus Subtypes and Genetic Screening for Virus Variants by High-Resolution Melting Analysis

Abstract: We assessed the use of high-resolution melting (HRM) analysis for the rapid identification of influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 41 publications
1
52
0
2
Order By: Relevance
“…As long as reference samples are included in the HRMA for each independent analysis, the HRMA profile can distinguish variants with differences in Tm values as little as 0.15°C. 17 This can be achieved by the use of average of HRM GCPs. However, variations in Tm values and discrepancies in GCPs were found among the tested samples in the current study when using ARMS qRT-PCR combined with HRMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As long as reference samples are included in the HRMA for each independent analysis, the HRMA profile can distinguish variants with differences in Tm values as little as 0.15°C. 17 This can be achieved by the use of average of HRM GCPs. However, variations in Tm values and discrepancies in GCPs were found among the tested samples in the current study when using ARMS qRT-PCR combined with HRMA.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since 2008, RT-PCR combined with the high-resolution melting (HRM) analysis (HRMA) has been used to detect several viruses, including Infectious bursal disease virus and Influenza A virus, and viruses within the genera Norovirus and Capripoxvirus. 8,17,28 The melting temperature (Tm) and the patterns of the HRM curves that are generated by denaturation of the various amplicons along a temperature gradient can be used to discriminate genetic variations in virus strains. 6 Accordingly, a RT-PCR assay combined with HRMA has also been reported for the Australian IBV wildtype and vaccine strains based on the hypervariable region of 3′-UTR.…”
Section: Introductionmentioning
confidence: 99%
“…40 . In the field of virology, Lin et al 41 developed high resolution melting analysis for subtype differentiation of the influenza A virus and for detection of newly emerging variants. The influenza B virus has also been studied using the melting curve analysis by Nakagawa et al 42 , who demonstrated that the assay not only detected its antigenic variants but also allowed for more precise analysis of the antigenic shifts in the influenza B virus.…”
Section: Melting Analysis For Genotyping Purposesmentioning
confidence: 99%
“…High resolution melting analysis (HRMA) of amplicons of fewer than 200 bp have been used for detection of single nucleotide polymorphisms, mutation scanning, and genotyping (Lin et al, 2008). The use of larger amplicons has been reported to reduce sensitivity and specificity of HRMA (Chou et al, 2005;Krypuy et al, 2006 The polymorphism of rabbit C-reactive protein promoter was investigated in two groups subjected to strict divergent selected rabbits according variation range of live-born kits at least after 3 litters.…”
Section: Introductionmentioning
confidence: 99%